Rice Farming in Tocantins: A Temporal Analysis of Production in Lagoa da Confusão - Blaszczyk , Luiz Antonio da Silva; Costa, Victor Hugo Santos; Araújo , Franscianne Batista de; Santos , João Paulo de Oliveira (Fronteira: Journal of Social, Technological and Environmental Science, 2025)
Brazil stands out as a global leader in rice production, with an annual output exceeding 11 million tons, ranking third among the grains cultivated in the country. Tocantins is the third-largest Brazilian rice producer, with cultivation concentrated primarily in the tropical floodplain region, particularly in the municipality of Lagoa da Confusão. Given the economic importance of rice farming for this region, understanding the interannual dynamics of rice production is crucial. Therefore, this study aimed to analyze the interannual dynamics of rice production in Lagoa da Confusão, Tocantins, between 2000 and 2023. Data from the IBGE Municipal Agricultural Survey (2000-2023) were used to analyze six variables related to rice production in the municipality. Principal component analysis (PCA) was also used to understand the interrelationships between the variables over time. The results showed that the area planted with rice in Lagoa da Confusão increased significantly, with production ranging from 53,820 tons in 2006 to 366,846 tons in 2017. Maximum productivity reached 7,323 kg/ha in 2017. The value of production increased from R 10.9 million in 2000 to R 729.1 million in 2023. The PCA revealed that production is strongly associated with the expansion of the cultivated area, while productivity had less influence on the volume produced.